PROJECT-BASED LEARNING ON STUDENTS' PROBLEM-SOLVING AND CRITICAL THINKING ABILITIES ON DATA CENTRALIZED MATERIAL IN CLASS X - Farasi, Dosni Roham Damai Setia; Tambunan, Hardi; Pangaribuan, Lena Rosdiana (Dharmas Education Journal (DE_Journal), 2023)
This study aims to determine the influence and effectiveness of project-based learning on students' problem-solving and critical thinking skills on data centering material in class X of SMA Negeri 1 Percut Sei Tuan in the academic year 2024/2025. This type of research is quantitative research with the research population being all students of class X of SMA Negeri 1 Percut Sei Tuan in the academic year 2024/2025. With purposive sampling technique, the research sample was obtained, namely classes X-7 and X-10. The instruments used were student learning outcome tests in the form of descriptions that had been validated, questionnaires to determine the achievement of effectiveness indicators, namely learning systematics, teacher communication and student responses, and student activity observation sheets. The results of the study showed that: (1) project-based learning has an effect on problem-solving skills (2) the effect of project-based learning on problem-solving skills is in the moderate category (3) project-based learning has an effect on students' critical thinking skills (4) the effect of project-based learning on students' critical thinking skills is in the moderate category (5) project-based learning is effective on problem-solving skills and (6) project-based learning is effective on students' critical thinking skills..